Recent Progress in Hydrogel-Based Bioinks for 3D Bioprinting: A Patent Landscape Analysis and Technology Updates - Saadan, Raja; Alaoui, Chaymaa Hachimi; Quraishi, Khurrum Shehzad; Afridi, Faisal; Chigr, Mohamed; Fatimi, Ahmed (Journal of Research Updates in Polymer Science, 2024)
Hydrogel-based bioinks have emerged as a critical component in the field of three-dimensional (3D) bioprinting, with numerous polymers being explored and utilized for this purpose. The high volume of patent applications reflects a competitive and dynamic research environment, where various entities are actively developing new formulations and applications for hydrogel-based bioinks. As this field continues to evolve, tracking these trends is essential for understanding the future direction of the technology and identifying key innovations and players in the industry. This study reveals substantial growth in the patent landscape for hydrogel-based bioinks in 3D bioprinting, with 173 patent documents published between 2013 and 2024. The marked increase in patent filings, particularly from 2018 onwards, underscores the growing recognition of the technologys potential in diverse applications, including tissue engineering and regenerative medicine. Although patent applications have outpaced granted patents, the steady rise in granted patents indicates the fields maturation and the transition of innovations from concept to legally protected technologies. The leading patent applicants in this domain include both industry leaders and academic institutions. Companies such as Organovo INC and Cellink AB are driving innovation through extensive patent activity, while academic institutions and foundations also make significant contributions, highlighting a robust ecosystem where industrial and academic research propel the technology forward. The global distribution of intellectual property filings in this field is broad, with significant activity in the United States, Europe, and Asia. This diversity in patenting jurisdictions reflects the global interest in advancing bioprinting technologies, particularly for healthcare applications. Patent classifications for hydrogel-based bioinks in 3D bioprinting illustrate the convergence of materials science, biotechnology, and advanced manufacturing. These classifications highlight the diverse applications of bioinks, ranging from tissue regeneration and stem cell therapy to the development of medical devices and multifunctional bioactive materials based on polymers.